VD_FINDINFO Arrêt / 2025 / 336 vom 20. Mai 2025 - VD Tribunal cantonal (2025)
MOYEN DE PREUVE, ADMISSION DE LA DEMANDE, OBSERVATION DU DÉLAI, OPPOSITION TARDIVE | 38 LPGA, 39 al. 1 LPGA, 52 al. 1 LPGA